Computational Design, Synthesis and Evaluation of Caffeine Imprinted Molecular Imprint Polymer (MIP) - Wan Mohd Akmal Wan Long (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Caffeine had been extensively studied in various fields due to its beneficial effect on human and in the same time it still has negative effects. Therefore, a suitable method is needed to isolate caffeine. In this research, molecular imprint polymer (MIP) was used to study the rebinding properties of caffeine in order to isolate from coffee. MIP possessed host-guest concept with highly specific recognition site using molecular template. A rational approach was taken to enhance the performance of MIP of caffeine by involving computational design, synthesis of MIP and evaluation through rebinding assay of caffeine. The experiment is started with computational design to simulate the polymer properties through molecular modelling using HyperChem 6.0 software. This molecular modelling is applied with AM1 (Austin Method 1) of semi empirical method with Polak-Ribiere algorithm to determine the suitable functional monomer and cross linker for MIP preparations. The ratio of 1:4, 1:4.5 and 1:5 for caffeine and itaconic acid as template and functional monomer respectively were expected to have a good binding properties in MIP synthesis. The caffeine was removed from MIP using Soxhlet extraction and left the cavities inside the MIP. Rebinding assay of caffeine inside the MIP was studied using spectroscopy. The result show that ratio 4 having high binding selectivity of caffeine which is 83 %.